1997
DOI: 10.1557/proc-469-529
|View full text |Cite
|
Sign up to set email alerts
|

Self-Diffusion as A Limiting Factor of a-SiGe Crystallization

Abstract: Highly doped (∼1018 to 1021cm−3) polycrystalline Si1-xGex films, crystallized from amorphous (a) state at relative low temperatures, are prospective materials in a variety of applications, such as liquid-crystal displays, solar cells and integrated thermoelectric sensors on large-area glass substrates. Since the nature of the grains in the crystallized film defines properties such as carrier mobility, the nucleation and growth process of the a-SiGe films is of fundamental interest. We have studied the crystall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
2
0

Year Published

1999
1999
2001
2001

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
2
2
0
Order By: Relevance
“…The change in n reflects a typical crystallization process in thin films, which starts as a 3D process when the crystals are small and transforms to a 2D process when the grain size D , reaches the film thickness d . When N is high and vg low, as was observed earlier in Sil-,Ge,v : H : B films (Edelman et al 1995) and Sil-,Ge, : Ga (Edelman et al 1996(Edelman et al , 1997, the crystallization resulted in a nanocrystalline structure, typical of a 3D mode, at temperatures between 500 and 850°C. However, in this case, the Sio.5Geo.5 films (both undoped and B doped) crystallized in a mode in which N is relatively low but wg is relatively high.…”
Section: Philosophical Magazinesupporting
confidence: 53%
“…The change in n reflects a typical crystallization process in thin films, which starts as a 3D process when the crystals are small and transforms to a 2D process when the grain size D , reaches the film thickness d . When N is high and vg low, as was observed earlier in Sil-,Ge,v : H : B films (Edelman et al 1995) and Sil-,Ge, : Ga (Edelman et al 1996(Edelman et al , 1997, the crystallization resulted in a nanocrystalline structure, typical of a 3D mode, at temperatures between 500 and 850°C. However, in this case, the Sio.5Geo.5 films (both undoped and B doped) crystallized in a mode in which N is relatively low but wg is relatively high.…”
Section: Philosophical Magazinesupporting
confidence: 53%
“…Rutherford backscattering spectroscopy ͑RBS͒ examination of the films showed that the O/Ti ratio is about 2/1, and no contaminations were detected by Auger electron spectroscopy ͑AES͒. 12 The sensing behavior during exposure to ambient oxygen between 100 and 325°C was reported in a previous paper. 15 The response is significant between 200 and 325°C, but a steady state is not attained within 1 h and the recovery is slower than the response, leading to a drift in the electrical conductance during exposure to successive pulses of oxygen.…”
supporting
confidence: 51%
“…The TiO 2 films were deposited on oxidized Si substrates with embedded Au interdigital electrodes, and were subsequently annealed at 400°C in vacuum ͑0.008 Pa͒ for 170 h. Microstructural characterization of the TiO 2 films was reported elsewhere. [12][13][14] The electrical conductance of TiO 2 specimens was monitored in an environmental chamber during exposure to air ͑practically oxy-gen͒ when the pressure inside the chamber increased from a base level of 0.008 to 3.1 Pa by letting air leak into the chamber for 1 h, and immediately afterwards during re-evacuation back to the base pressure for another 1 h. It took ϳ1 min for the system to pressurize and ϳ1 s to re-evacuate. These tests were done at constant temperatures between 100 and 325°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation